2018
DOI: 10.1002/tcr.201800149
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Nanomaterials Designed from Natural Supramolecular Systems

Abstract: Natural supramolecular assemblies exhibit unique structural and functional properties that have been optimized over the course of evolution. Inspired by these natural systems, various bio‐nanomaterials have been developed using peptides, proteins, and nucleic acids as components. Peptides are attractive building blocks because they enable the important domains of natural protein assemblies to be isolated and optimized while retaining the original structures and functions. Furthermore, the peptide subunits can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 160 publications
(261 reference statements)
0
23
0
Order By: Relevance
“…Microtubules are hollow tubular protein assemblies composed of intracellular α-/β- tubulin dimers with significant nanodevice implications attributed to their involvement in many eukaryotic cell functions including tumor progression. Peptide-modulated nanodevice-encapsulating drugs targeting intracellular tubulins under different formulations such as peptide-conjugating liposomes or peptide-drug assemblies to exert synergistic anti-cancer effects have attracted vast attentions [88,89]. A recent pioneer study further demonstrated that peptides selected from microtubule-associated protein Tau functionalized inner surface of microtubule by encapsulation of gold nanoparticles inside microtubules [90].…”
Section: Innovations and Computational Methods For Peptide—proteinmentioning
confidence: 99%
“…Microtubules are hollow tubular protein assemblies composed of intracellular α-/β- tubulin dimers with significant nanodevice implications attributed to their involvement in many eukaryotic cell functions including tumor progression. Peptide-modulated nanodevice-encapsulating drugs targeting intracellular tubulins under different formulations such as peptide-conjugating liposomes or peptide-drug assemblies to exert synergistic anti-cancer effects have attracted vast attentions [88,89]. A recent pioneer study further demonstrated that peptides selected from microtubule-associated protein Tau functionalized inner surface of microtubule by encapsulation of gold nanoparticles inside microtubules [90].…”
Section: Innovations and Computational Methods For Peptide—proteinmentioning
confidence: 99%
“…Peptides are small, and thus easy to synthesize and to permeate the cell membranes. In addition to their small size, peptides can be derived from natural proteins, and they can be engineered to maintain the unique structural and functional properties of the natural protein [68,69]. Peptides can also be modified easily [70] and are less immunogenic compared to proteins and antibodies [71].…”
Section: Discussionmentioning
confidence: 99%
“…The selfassembling peptides are able to serve this resolute as scaffolds. The special focus in the review articles of hydrogels and porous scaffolds remains in controlled release of drugs from the tissue engineering platforms (Boekhoven and Stupp, 2014;Loo et al, 2015;Rambhia and Ma, 2015;Koutsopoulos, 2016;Banerjee et al, 2018;Lee, 2018;Inaba and Matsuura, 2019). One of the very important areas in tissue engineering is to explore the ways, to modify the properties of the materials, including mechanical and chemical functionality through changes at the sequence level to influence the cell behavior and modulate the scaffold stability (Zhou et al, 2014).…”
Section: Applications Of Peptide Self-assembliesmentioning
confidence: 99%
“…Beyond the biological functions, designing peptides, with desired structures and functions by mimicking natural supramolecular systems, are in the air which can provide innovative designing principles to intricate "molecular robots" as next-generation peptide nanomaterials (Inaba and Matsuura, 2019). Handelman et al (2016b) studied the reconstructive phase transition exhibited by some of the self-assembled ultrashort di-and tripeptide nanostructures to modify optoelectronic properties followed by the appearance of visible photoluminescence.…”
Section: Applications Of Peptide Self-assembliesmentioning
confidence: 99%